The magnetic properties of potassium holmium double tungstate - Borowiec, M.T.; Hoffmann, J.-U.; Prokes, K.; Woźniak, K.; Dobrzycki, Ł.; Barański, M.; Domukhovski, V.; Shtyrkhunova, V.; Żmija, J.; Michalski, E.; Majchrowski, A.; Dyakonov, V.P.; et al. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The magnetic investigations of potassium holmium double tungstate KHo(WO4)2 have been performed. The results of measurements of magnetic susceptibility and magnetization as a function of temperature (T from 0.3 K up to 100 K) and magnetic field (up to 1.5 T) are presented. A strong anisotropy of magnetic properties wasfound. The magnetic measurements data were used to calculate the interaction energy. It was shown that the interactions between nearest neighbors Ho3+ ions have antiferromagnetic character.